Using social media effectively in the classroom : blogs, wikis, twitter, and more - Seo, Kay Kyeong-Ju. (New York : Routledge, 2013)
"The rapid expansion of blogs, Twitter, wikis, and virtual worlds has dramatically transformed the landscape of education. Through highly accessible networks, these new media can integrate students into a learning community by enabling them to create, customize, and share content online. Using Social Media Effectively in the Classroom shows educators how to: utilize social media to best support learners resolve potential problems create a powerful sense of community within user-centered Web 2.0 technologies. Moving beyond basic explanations of technologies and how to use them, Using Social Media Effectively in the Classroom provides research-based, jargon-free, practical examples of what works, what doesn't, and why when it comes to social media. Organized according to the systemic process of instructional design, contributors describe innovative strategies for incorporating social media into educational settings as well as significant issues to be taken into consideration at each phase of planning, designing, teaching, and evaluation"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Internet in education; Social media; Education -- Effect of technological innovations on; Electronic books